Modern Language Techniques from Emerging Trends, Evaluation, Obstacles, to Prospects: Review - Hussain , Samira; Alshibani, Dina; Yousif, Noor (Journal of Applied Engineering and Technological Science (JAETS), 2025)
Languages designed for a particular application domain are known as domain-specific languages (DSLs). When compared to general-purpose programming languages (GPPLs) in their field of usage, they provide significant improvements in expressiveness and usability. In order to handle the concurrent expansion of areas like cloud-native, distributed, and modular architectures, this discipline has been undergoing enormous evolution. Finding current trends, gaps, and new prospects in the field of DSLs is the aim of this review. We use a novel approach in this review by grouping the state-of-the-art studies into several groups. Furthermore, the three primary implementation issues of DSLs abstract syntax, concrete syntax, and semantics were highlighted. In particular, they are distinguished by the functions they prioritize (modeling, visualizing), the mapping outcomes (textual/graphical symbols), and their parsing and mapping approach (external/internal) between the abstract and concrete languages. Focus on the development lifecycle while keeping up with contemporary trends, obstacles, and the assessment metrics that are employed to evaluate the DSLs. We concluded by summarizing the research overview of DSLs after integrating it with the literature.